(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The rational use of lasers as sources of radiation is also related to the development of optical systems for conversion of laser radiation. One of the ways to convert the laser radiation is related to its collimation, changing the cross-section and changing the divergence. This article presents a methodology for designing two component optical systems to reduce the divergence of laser beams. Ready-made optical elements were used, with which three different configurations were created and analyzed. The optical design was developed and subsequent optimization was performed. The resulting system has diffraction-limited quality of the outgoing laser beam and small dimensions.